2021
DOI: 10.3389/fmicb.2021.713513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microbial Diversity and Dynamics During Bacon Storage Inoculated With Potential Spoilage Bacteria by High-Throughput Sequencing

Abstract: Staphylococcus xylosus, Leuconostoc mesenteroides, Carnobacterium maltaromaticum, Leuconostoc gelidum, and Serratia liquefaciens were investigated for their roles in in the spoilage of sterilized smoked bacon. These five strains, individually and in combination, were applied as starters on sliced bacon at 4–5 log10 CFU/g using a hand-operated spraying bottle and stored for 45 days at 0–4°C. Dynamics, diversity, and succession of microbial community during storage of samples were studied by high-throughput sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…In CK, however, S. xylosus and S. vitulinus were barely detected, being replaced by a large amount of Carnobacterium divergens , Weissella viridescens , Leuconostoc carnosum and L. sakei . Among them, C. divergens , W. viridescens and L. carnosum could cause the spoilage of meat products 11 . Some studies had certified that the addition of Staphylococcus species to fermented products could improve the safety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In CK, however, S. xylosus and S. vitulinus were barely detected, being replaced by a large amount of Carnobacterium divergens , Weissella viridescens , Leuconostoc carnosum and L. sakei . Among them, C. divergens , W. viridescens and L. carnosum could cause the spoilage of meat products 11 . Some studies had certified that the addition of Staphylococcus species to fermented products could improve the safety.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, C. divergens, W. viridescens and L. carnosum could cause the spoilage of meat products. 11 Some studies had certified that the addition of Staphylococcus species to fermented products could improve the safety. Leroy et al 18 proposed that S. xylosus could inhibit the formation of S. aureus biofilms, and Casquete et al 6 observed an increased acidity and decreased coliforms in Iberian drysausage as a result of the inoculation of S. vitulinus.…”
Section: Composition Of Microbial Communities In Dry-cured Baconmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these associated VOCs can then be used to design models or an intelligent facility for predicting the deterioration of meat products. To our knowledge, few studies have assessed the VOCs corresponding to metabolites generated by the isolated major bacteria responsible for the spoilage in smoked bacon 19,20 …”
Section: Introductionmentioning
confidence: 99%